Considerations for Upscaling of Organohalide Perovskite Solar Cells. Issue 2 (30th November 2016) - Lin, Qianqian; Nagiri, Ravi Chandra Raju; Burn, Paul L.; Meredith, Paul
Abstract : Thin film organohalide lead perovskite‐based solar cells have emerged over the last five years as a potentially low‐cost, low‐embedded‐energy and high‐efficiency photovoltaic technology. However, almost all reported high‐efficiency devices have small active areas significantly less than 1 cm 2 . Upscaling of organohalide lead perovskite solar cells is now required for successful manufacturing and commercialization. In this work, three generic design rules for large area devices are proposed. Using these design rules, high efficiency large area (2.0 cm 2 ) cells are demonstrated based on a predictive methodology incorporating the optoelectronic design of highly transparent and conductive electrodes, and controlled crystal size and uniformity of the organohalide perovskite junction. These optimized large area monolithic solar cells show power conversion efficiencies (PCEs) >12%, with an enhanced open‐circuit voltage ( V oc ) of 1.02 V and respectable fill factor (FF) of 0.61. Abstract : Upscaling of organohalide lead perovskite solar cells is now required for successful manufacturing and commercialization. High‐efficiency large area (2.0 cm 2 ) devices are achieved based on a predictive methodology incorporating the optoelectronic design of highly transparent and conductive electrodes, and controlled uniformity of the organohalide perovskite junction.